Influence of Vocalized Reading Practice on English Learning and Psychological Problems of Middle School Students - Zhang, Hongyan; Han, Xianghua (Frontiers in Psychology, 2021)
The purpose is to improve the English learning anxiety and learning effect for middle school students. From the perspective of educational psychology, the influence of vocalized reading practice on students' English learning is studied based on the self-efficacy theory and the schema theory. To encourage students to practice English, the study might solve the problem of insufficient opportunities by applying the artificial intelligence (AI) chat system to students’ oral English practice. Several research hypotheses are put forward, which concern the correlation between students' English learning anxiety with their self-efficacy, topic familiarity, and English grades under vocalized reading practice. Then, the hypotheses are verified through a controlled trial and a questionnaire survey (QS). Afterward, the experimental and QS data are statistically analyzed and tested with a regression model. The results show that the students' English grades, self-efficacy, and topic familiarity have been significantly improved in the experimental group after the vocalized reading practice. The significance coefficient of the regression model is P=.000<0.05, which can be used to verify the proposed hypotheses. English grades, self-efficacy, and topic familiarity can well-predict students’ English learning anxiety. The Computer Simulation in Educational Communication (CSIEC) teaching system and AI can help create an interactive learning environment for students to practice oral English by chatting with AI robots.